THE INFLUENCE OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE JOB SATISFACTION AT THE SECRETARIAT OF THE SOUTH JAKARTA CITY ADMINISTRATION - Yulia Mujiaty; Deasy Novayanti; Darma Wijaya; Siti Nurjanah; Nisa Kurnia Zahra (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
In the era of intense global competition, organizations are increasingly required to adapt, innovate, and improve internal condition, including the creation of a conducive work environment that enhances employee comfort and motivation. This study aims to invatigate the influence of leadership style and organization culture on employee job satisfaction within Sekretariat Kota Administarsi Jakarta Selatan. Utilizing a quantitative research approach, data were collected through a survey involving 35 respondents. The data analysis was conducted using statistical software SPSS (Version 25). The result of the F-test showed a significance value of 0,000 < 0,05, indicating that leadership style and organizational culture have a statistically significant effect on job satisfaction. Therefore, the research confirms that both variables play an important role in shaping employee satisfaction levels and hypothesis H3 is accepted. These finding emphasize the importance of effective leadership and a supportive organizational culture in enhancing workplace satisfaction